Visible‐Light‐Mediated Generation of Nitrogen‐Centered Radicals: Metal‐Free Hydroimination and Iminohydroxylation Cyclization Reactions. Issue 47 (28th September 2015) - Davies, Jacob; Booth, Samuel G.; Essafi, Stephanie; Dryfe, Robert A. W.; Leonori, Daniele
Abstract: The formation and use of iminyl radicals in novel and divergent hydroimination and iminohydroxylation cyclization reactions has been accomplished through the design of a new class of reactive O ‐aryl oximes. Owing to their low reduction potentials, the inexpensive organic dye eosin Y could be used as the photocatalyst of the organocatalytic hydroimination reaction. Furthermore, reaction conditions for a unique iminohydroxylation were identified; visible‐light‐mediated electron transfer from novel electron donor–acceptor complexes of the oximes and Et3 N was proposed as a key step of this process. Abstract : Divergent SET : Visible‐light irradiation of O ‐aryl oximes leads to the generation of N‐centered radicals. Depending on the reaction conditions, these radicals cyclize either in a photoredox‐catalyzed hydroimination or in an iminohydroxylation via electron donor–acceptor complexes (EY=eosin Y).